ANALISIS TERHADAP TATA KELOLA PERBANKAN SYARIAH DALAM MENJAGA KINERJANYA - Harjoni Harjoni (IAIN Lhokseumawe, 2021)
Implementation of governance in Islamic banking is expected to increase trust and increase added value for all interested parties. This study aims to examine impact of Non Performing Financing, Efficiency (BOPO), Fraud and Good Corporate Governance Influence on Profitability on sharia Commercial Bank in Indonesia. The independent variables used in this study are first, Non-Performing Financing, Secondly, Efficiency (BOPO), third, Fraud, fourth, the Sharia Supervisory Board and fifth, Audit Committee. While the dependent variable of this study is Profitability. The research method uses secondary data in the form of annual reports and good corporate governance reports of Islamic banks in Indonesia. The results showed a significant influence between BOPO and Audit Commitee on Profitability and insignificant influence between NPF, Fraud and the Sharia Supervisory Board on Profitability. Future studies are expected to test by adding other variables.